Melampaui dikotomi personal-komunal: Sebuah sintesis hermeneutis untuk pendidikan Kristiani - Kristiani (KURIOS, 2026)
Christian education has long been trapped in the dichotomy between personal Bible reading and communal interpretation. This article proposes a hermeneutical synthesis that transcends this binary opposition by drawing on philosophical hermeneutics and ecclesiological theology. Through library research employing a conceptual analysis, this study argues that Scripture reading is neither purely individual nor merely collective but constitutes a dialectical process in which personal encounter with the text occurs within and is shaped by interpretive communities. The synthesis offers four dimensions: historical consciousness, communal dialogue, spiritual formation, and pneumatological participation. This framework reconceptualizes Christian education from information transfer toward transformative formation within reading communities. The article concludes that effective Christian education requires pedagogical designs acknowledging Scripture as both personally addressed and communally mediated.   Abstrak Pendidikan Kristiani telah lama terjebak dalam dikotomi antara pembacaan Alkitab secara personal dan interpretasi komunal. Artikel ini mengusulkan sintesis hermeneutis yang melampaui oposisi biner tersebut dengan berpijak pada hermeneutika filosofis dan teologi eklesiologis. Melalui penelitian kepustakaan dengan metode analisis konseptual, studi ini berargumen bahwa pembacaan Alkitab bukanlah murni individual maupun sekadar kolektif, melainkan merupakan proses dialektis di mana perjumpaan personal dengan teks terjadi di dalam dan dibentuk oleh komunitas interpretatif. Sintesis ini menawarkan empat dimensi: kesadaran historis, dialog komunal, formasi spiritual, dan partisipasi pneumatologis. Kerangka ini merekonseptualisasi pendidikan Kristiani dari transfer informasi menuju formasi transformatif dalam komunitas pembaca. Artikel menyimpulkan bahwa pendidikan Kristiani yang efektif memerlukan desain pedagogis yang mengakui Alkitab sebagai yang ditujukan secara personal sekaligus dimediasi secara komunal.